2011
DOI: 10.1371/journal.pone.0027463
|View full text |Cite
|
Sign up to set email alerts
|

Early Antiretroviral Therapy During Primary HIV-1 Infection Results in a Transient Reduction of the Viral Setpoint upon Treatment Interruption

Abstract: BackgroundLong-term benefits of combination antiretroviral therapy (cART) initiation during primary HIV-1 infection are debated.MethodsThe evolution of plasma HIV-RNA (432 measurements) and cell-associated HIV-DNA (325 measurements) after cessation of cART (median exposure 18 months) was described for 33 participants from the Zurich Primary HIV Infection Study using linear regression and compared with 545 measurements from 79 untreated controls with clinically diagnosed primary HIV infection, respectively a kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Other animal studies showed that HIV-1 always rebounded after ART was withdrawn in these setting 19,20 . However, our study showed that hu-BLT mice which received ART at 6 hours post-infection had undetectable PVL measured by the sensitive ddPCR after ART was stopped.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other animal studies showed that HIV-1 always rebounded after ART was withdrawn in these setting 19,20 . However, our study showed that hu-BLT mice which received ART at 6 hours post-infection had undetectable PVL measured by the sensitive ddPCR after ART was stopped.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have shown that ART administration within days of post-infection (p.i.) often resulted in a rebound of viremia during treatment interruption 19,20 . In contrast, the Mississippi infant case initiated ART at ∼30 hours after birth was able to suppress viremia for 2 years without ART 6,7 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent RT-SHIV mne EFV monotherapy study using an ultrasensitive allele-specific PCR method demonstrated that EFV drug resistance mutations existed at low frequencies within the circulating virus population at 13 weeks postinfection, prior to the initiation of therapy [31*]. Early cART initiation has been shown to impact the magnitude of later, off-treatment viremia rebound, however, suggesting that cART timing may influence the seeding and establishment of the latent viral reservoir and/or the development of antiviral immune responses [37,61,6468], similar to findings for humans treated during acute infection [6971*]. It remains possible that initiating therapy later in infection might benefit from the additive impact of adaptive immune responses, and several studies have demonstrated good virologic suppression when cART was initiated later in infection [8,9,14,59*].…”
Section: Cart Drugsmentioning
confidence: 92%
“…Administration of antiretroviral therapy in very early acute infection appears to result in a lower post-treatment total and integrated DNA and HIV-RNA levels, suggesting aggressive treatment can limit the size of the viral reservoir 1, 79 . Although early treatment can substantially reduce the total reservoir size, a stable population of latently infected CD4 cells exists that transits in to the long-lived latent reservoir and is relatively unaffected by early cART 10 .…”
Section: Hiv Reservoirs: Obstacles To a Curementioning
confidence: 99%